Novel diaphragm-free solid-state battery and preparation method of composite pole piece of novel diaphragm-free solid-state battery

By adopting a solid-state battery design without a membrane in lithium-ion batteries, using solid-state composite polymer electrolyte and lithium salt ceramic layers to replace traditional membranes, the problems of low energy density and poor safety of lithium-ion batteries are solved, and higher battery safety is achieved sex and migration rate.

CN119208774APending Publication Date: 2024-12-27HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411308194.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have low energy density and poor safety, especially due to the risk of short circuit and explosion caused by the prone to failure of the diaphragm materials at abnormal temperatures, as well as the problems of large interface impedance and poor cycle stability of solid electrolytes.

Method used

Using a solid-state battery design without a membrane, polyoxyethylene, polyethyleneimine, polyethyleneimine is used to cover the solid-state composite polymer electrolyte layer on the surface of the positive electrode sheet and lithium salt ceramic layer on the surface of the negative electrode sheet. The composite polymer electrolyte composed of inorganic lithium salts, additives and plasticizers increases the migration rate of lithium ions and increases the conductivity and mechanical strength through the lithium salt ceramic layer.

Benefits of technology

It achieves leakage-free, low self-discharge rate and improves the safety performance of lithium-ion batteries, enhances the thermal shutdown capability and mechanical strength of the battery, and reduces the explosion risk of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049885220000071
    Figure BDA0005049885220000071
  • Figure BDA0005049885220000081
    Figure BDA0005049885220000081
Patent Text Reader

Abstract

The invention provides a novel diaphragm-free solid-state battery and a preparation method of a composite pole piece of the novel diaphragm-free solid-state battery, and belongs to the technical field of lithium batteries. The diaphragm-free solid-state battery comprises a composite positive plate and a composite negative plate, the composite positive plate comprises a positive plate and a solid-state composite polymer electrolyte layer covering the surface of the positive plate, and the solid-state composite polymer electrolyte layer comprises polyoxyethylene, polyethyleneimine, inorganic lithium salt, an additive and a plasticizer. The electrolyte layer has the function of a thermal turn-off coating, pores among particles at normal temperature can ensure smooth back-and-forth penetration of lithium ions, coating particles are fused and collapsed at a relatively high temperature to isolate the lithium ions from passing, and the safety performance of the lithium ion battery is improved; the composite negative plate comprises a negative plate and a lithium salt ceramic layer covering the surface of the negative plate, can provide active lithium and can play a role in isolating a positive electrode and a negative electrode together with the solid electrolyte, a diaphragm is not needed any more, and the safety performance of the battery is greatly improved while the active lithium is supplemented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a novel diaphragm-free solid-state battery and a preparation method of a composite pole piece thereof. Background Art

[0002] With the rapid development of lithium-ion battery technology and its extensive application in electric vehicles and electronic consumer products, people have put forward higher requirements on the safety performance of lithium-ion batteries. However, due to the limitations of traditional lithium-ion battery materials, the improvement of energy density is usually achieved at the expense of safety. For example, a high-nickel positive electrode with poor thermal stability is usually matched with a silicon-carbon negative electrode with higher capacity but greater expansion. These two are difficult to further improve.

[0003] Usually, the main components of lithium-ion batteries are positive electrode, negative electrode, diaphragm, electrolyte and current collector. The main components of the electrolyte include solvents, additives and lithium salts, which are responsible for transferring lithium ions and providing some active lithium inside the battery. The diaphragm is a specially formed polymer film with a microporous structure. Its main function is to separate the positive and negative electrodes of the battery to prevent direct contact, allowing lithium ions to pass freely while insulating electrons. At present, the materials of diaphragms are all organic polymer materials, usually composed of PE or PP. This material has two main problems: on the one hand, when the battery or battery system is abnormally heated, it will shrink, melt or even carbonize, causing large-area contact between the positive and negative electrodes and short circuit or even explosion; on the other hand, impurities and burrs in the battery may also pierce the diaphragm, causing direct contact between the positive and negative electrodes and short circuit.

[0004] At present, in order to solve the problems of low energy density and poor safety of lithium-ion batteries, the research direction is to develop solid-state lithium-ion batteries. Solid-state lithium-ion batteries use non-flammable solid electrolytes instead of traditional liquid electrolytes, which can greatly improve the safety of lithium-ion batteries and have broad application prospects. However, due to the disadvantages of large interface resistance, low energy density and poor cycle stability, the commercialization process of solid electrolytes has been hindered. Summary of the invention

[0005] In view of the technical problems existing in the prior art, the present invention provides a new type of solid-state battery without diaphragm and a composite electrode thereof.

[0006] The technical solution of the present invention is as follows:

[0007] In a first aspect of the present invention, a composite positive electrode sheet is provided, comprising a positive electrode sheet and a solid composite polymer electrolyte layer covering the surface of the positive electrode sheet, wherein the solid composite polymer electrolyte layer comprises 10 to 30 parts by mass of polyethylene oxide, 20 to 50 parts by mass of polyethylene imine, 5 to 40 parts by mass of an inorganic lithium salt, 5 to 15 parts by mass of an additive and 5 to 30 parts by mass of a plasticizer.

[0008] Solid composite polymer electrolytes have many advantages, such as good flexibility, thin layer, no leakage of batteries prepared with them, and low self-discharge rate, and have the application prospect of replacing liquid electrolytes in secondary batteries. In solid composite polymer electrolytes, lithium ions are mainly transferred by the free movement of polymer chain segments. Because the transmission rate of lithium ions in the amorphous region is 2-3 orders of magnitude higher than that in the crystalline region, the selected polymer needs to be modified by doping and other methods to be in a highly elastic state or viscous flow state at room temperature.

[0009] Furthermore, the solid composite polymer electrolyte layer has a thickness of 10-20 μm, preferably 15-20 μm;

[0010] Furthermore, the relative molecular mass of the polyoxyethylene is between 8000 and 60000, preferably 8000, 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000, 55000 or 60000.

[0011] Furthermore, the relative molecular mass of the polyethyleneimine is between 3000 and 10000, preferably 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000.

[0012] Since the alkoxy groups in the solid composite polymer electrolyte can coordinate with lithium ions to dissolve the lithium salt, the lithium ions in the solid composite polymer electrolyte mainly rely on the segmental movement of polyethylene oxide to achieve migration. During the migration of lithium ions, the strong attraction and coordination of alkoxy groups on lithium ions reduce the migration rate of carriers. In order to eliminate this effect, adding polyethyleneimine to polyethylene oxide reduces the attraction and coordination of the matrix on lithium ions, which can increase the migration rate of lithium ions.

[0013] Furthermore, the inorganic lithium salt includes one or more of lithium fluoromethanesulfonate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium perchlorate, and lithium aluminate.

[0014] Furthermore, the additive is selected from one of aluminum oxide, silicon oxide, silicon oxide and polysiloxane.

[0015] Furthermore, the plasticizer includes vinyl carbonate EC or vinyl carbonate VEC.

[0016] Since the migration of lithium ions mainly occurs in the amorphous region, the additives added to the system can be dispersed between the polymer chain segments, effectively preventing the regular arrangement of the polymer, making it highly amorphous and reducing the crystallinity of the system. At the same time, with the addition of plasticizers, the small molecules of the plasticizers will be inserted between the polymer molecular chains, weakening the attraction between the polymer molecular chains, increasing the distance between the molecular chains, reducing the entanglement between the polymer molecular chains, and increasing the migration rate of lithium ions.

[0017] A second aspect of the present invention provides a solid-state battery without a separator, comprising the composite positive electrode sheet described above.

[0018] Furthermore, the membrane-free solid-state battery also includes a negative electrode plate, the surface of which is covered with a lithium salt ceramic layer, and the lithium salt ceramic components include polyvinylidene fluoride PVDF, lithium aluminum titanium phosphate and aluminum oxide, with a mass ratio of 1 to 3:3 to 5:8 to 12, for example, the ratio can be 3:5:12, 2:4:10, 3:4:9.

[0019] Furthermore, the thickness of the lithium salt ceramic layer is 5-20 μm, preferably 5-15 μm, and more preferably 5-10 μm.

[0020] Among them, the lithium salt ceramic layer is not afraid of piercing by foreign objects such as lithium dendrites and burrs, and can improve the electrical conductivity and mechanical strength of lithium-ion batteries.

[0021] Among them, a lithium salt ceramic layer is coated on the surface of the negative electrode, and a solid composite polymer electrolyte layer is coated on the surface of the positive electrode to replace the separator. On the one hand, the inorganic lithium salt ceramic layer has lithium ion conduction and high strength and is not afraid of piercing by foreign objects such as lithium dendrites and burrs, thereby improving the conductivity and mechanical strength of the lithium-ion battery; on the other hand, the organic solid composite polymer electrolyte layer has a thermal shutdown coating function. At room temperature, the pores between particles can ensure the smooth reciprocating interlacing of lithium ions, and at higher temperatures, the coating particles can melt and collapse to isolate the passage of lithium ions, thereby improving the safety performance of lithium-ion batteries.

[0022] A third aspect of the present invention provides a method for preparing a solid-state battery without a diaphragm, comprising the following steps:

[0023] preparing a composite positive electrode sheet, including coating a solid composite polymer electrolyte on the surface of the positive electrode sheet and then drying it;

[0024] A diaphragm-free solid-state battery is obtained through the processes of rolling, slitting, laser cutting, die cutting, lamination, assembly, baking, formation and capacity division.

[0025] Preferably, the method for preparing the diaphragm-free solid-state battery also includes preparing a composite negative electrode sheet, including coating a lithium salt ceramic on the surface of the negative electrode sheet and then drying it; and obtaining a diaphragm-free solid-state battery through the processes of rolling, slitting, laser cutting, die cutting, lamination, assembly, baking, formation, and capacity separation.

[0026] Furthermore, the solid composite polymer electrolyte is prepared by the following method: placing polyoxyethylene, polyethyleneimine, inorganic lithium salt, additives and plasticizers in an oven at 60-80°C for 8-12 hours for drying and storage; taking an appropriate amount of NMP as a solvent, adding an appropriate amount of PVDF and stirring it thoroughly until it is completely dissolved, then adding polyoxyethylene, polyethyleneimine and plasticizers respectively, stirring them thoroughly to dissolve, and then adding inorganic lithium salts and additives at room temperature, ultrasonically stirring, and magnetically stirring for 3-5 hours to disperse them evenly into a slurry for later use;

[0027] The positive electrode sheet includes a positive electrode active material and a positive electrode current collector, and may also include a binder and a conductive agent;

[0028] The positive electrode current collector is selected from any one of aluminum foil, copper foil, nickel foil, zinc foil and titanium foil;

[0029] Preferably, the positive electrode current collector is an aluminum foil of 10-15 μm;

[0030] The positive electrode active material is selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich lithium manganese oxide, lithium iron phosphate, lithium vanadium phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium manganese iron phosphate, lithium cobalt iron phosphate, and lithium nickel iron phosphate.

[0031] Furthermore, the lithium salt ceramic is prepared by the following method: using NMP as a solvent, first adding polyvinylidene fluoride to dissolve, then adding lithium aluminum titanium phosphate and aluminum oxide and stirring to obtain a lithium salt ceramic slurry for use.

[0032] The negative electrode sheet includes a negative electrode active material and a negative electrode current collector, and may also include a binder and a conductive agent;

[0033] The negative electrode active material is selected from at least one of graphite, graphene, mesophase carbon microspheres, metallic lithium, hard carbon, soft carbon, silicon dioxide, lithium titanate, silicon, tin, and germanium;

[0034] The negative electrode current collector is selected from any one of aluminum foil, copper foil, nickel foil, zinc foil and titanium foil;

[0035] Preferably, the negative electrode current collector is 4-7 μm copper foil.

[0036] The stacking sheets are preferably formed by a Z-type stacking hot pressing process with tabs on both sides, and then packaged by an aluminum-plastic film.

[0037] The diaphragm-free solid-state battery provided by the present invention is not only suitable for soft-pack lithium batteries, but also for square and cylindrical batteries; the processing of battery cells (composite positive electrode sheets, composite negative electrode sheets) can also adopt lamination, thermal composite or winding process paths accordingly.

[0038] The diaphragm-free solid-state battery provided by the present invention includes a solid composite polymer electrolyte composite positive electrode sheet and a lithium salt ceramic composite negative electrode sheet. The solid electrolyte is a blend of organic polymers and inorganic lithium salts, etc. The solid electrolyte contains specific functional groups, including coordinated anion groups, and the cations corresponding to the anion groups are lithium ions. The solid electrolyte is between the positive electrode active material and the negative electrode active material. The lithium salt ceramic layer is coated on the surface of the negative electrode active material, which can play two roles: providing active lithium; and can play the role of isolating the positive and negative electrodes together with the solid electrolyte, and no diaphragm is needed. The supplement of active lithium greatly improves the safety performance of the battery.

[0039] Other features and advantages of the present invention will be described in the following description, and partly become obvious from the description, or be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures and methods pointed out in the description. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the implementation scheme of the present application will be described in detail below in conjunction with specific examples. The technical terms and scientific terms used in the present invention have the meanings generally understood by ordinary technicians in the technical field to which the present invention belongs, without other definitions. Without departing from the concept of the present invention, those skilled in the art may make various improvements and changes to the specific implementation methods of the present invention specification, which all belong to the protection scope of the present invention. Unless otherwise specified, the chemical reagents, raw materials, etc. selected herein can be purchased from commercial channels.

[0041] The following uses the technical solution of the present invention to prepare and test the performance of a solid-state battery without a diaphragm:

[0042] Example 1

[0043] (1) Pulping

[0044] Prepare negative electrode slurry: slurry graphite: conductive carbon black SP: sodium carboxymethyl cellulose CMC: styrene butadiene rubber SBR = 96.2%: 1.0%: 1.2%: 1.6%, and obtain a slurry with a viscosity of 6000 mPas and a solid content of 55% after homogenization;

[0045] Preparation of positive electrode slurry: The main material used is NCM ternary nickel-cobalt-manganese material, in addition to multi-walled carbon nanotubes and polyvinylidene fluoride PVDF, among which NCM: multi-walled carbon nanotubes: polyvinylidene fluoride = 97.8%: 1.1%: 1.1%, the finished slurry viscosity is 5000mPas, and the solid content is 73.1%.

[0046] Preparation of solid composite polymer electrolyte: Polyoxyethylene, polyethyleneimine, lithium perchlorate, aluminum oxide and vinyl carbonate are placed in an oven at 80℃ for 10 hours to dry and store; take an appropriate amount of N-methylpyrrolidone (NMP) as a solvent, add an appropriate amount of PVDF, stir thoroughly until completely dissolved, the solid content of PVDF in NMP is 8%, then add polyoxyethylene, polyethyleneimine and plasticizer (vinyl carbonate) respectively, stir thoroughly to dissolve; add inorganic lithium salt (lithium perchlorate) and additive (aluminum oxide) to the above solution, ultrasonically and magnetically stir for 3 hours at room temperature, and disperse evenly for use. The mass ratio of polyoxyethylene, polyethyleneimine, lithium perchlorate, aluminum oxide and vinyl carbonate is 35:25:10:2:12, and the viscosity is 3000±1000mPas.

[0047] Preparation of lithium salt ceramics: Using N-methylpyrrolidone (NMP) as a solvent, first add polyvinylidene fluoride and stir at high speed until it is completely dissolved; add lithium aluminum titanium phosphate and aluminum oxide to the above solution respectively and stir again at high speed for 2-4 hours to prepare a lithium salt ceramic slurry. The lithium salt ceramic components are binder polyvinylidene fluoride, lithium aluminum titanium phosphate and aluminum oxide in a mass ratio of 3:5:12, the slurry viscosity is 2000±1000mPas, and the solid content is 25%.

[0048] (2) Electrode preparation

[0049] Composite positive electrode sheet preparation: 12μm aluminum foil is used to coat the positive electrode active material, with a surface density of 360g / m 2 After baking and drying, a solid composite polymer electrolyte layer with a thickness of 15 μm is coated on the surface of the positive electrode.

[0050] Composite negative electrode sheet preparation: 6μm copper foil is used to coat the negative electrode active material, with a surface density of 236g / m 2 After baking and drying, a lithium salt ceramic layer with a thickness of 8μm is coated on the surface of the negative electrode.

[0051] The prepared composite positive and negative electrode sheets are rolled, slit, laser cut and die cut to obtain the required electrode sheet size. The specification size of the negative electrode sheet is 99*237mm, and the specification size of the positive electrode sheet is 97*233mm.

[0052] (3) Battery production

[0053] The composite positive electrode sheets and the composite negative electrode sheets are placed alternately in a Z-type stack to prepare a battery cell with 23 positive electrodes and 24 negative electrodes. After aluminum-plastic film packaging, high-temperature formation at 60°C and capacity separation, a diaphragm-free solid-state battery is obtained.

[0054] Example 2

[0055] Compared with Example 1, the inorganic lithium salt is replaced with lithium aluminate LiAlO2, the dosage remains unchanged, and the other aspects remain the same.

[0056] Example 3

[0057] Compared with Example 1, the additive was changed to silicon dioxide, the dosage remained unchanged, and the other aspects remained the same.

[0058] Example 4

[0059] Compared with Example 1, the plasticizer was changed to vinyl ethylene carbonate (VEC), the dosage remained unchanged, and the other parameters remained the same.

[0060] Comparative Example 1

[0061] Compared with Example 1, the solid composite polymer electrolyte does not contain inorganic lithium salt, and the other aspects remain the same.

[0062] Comparative Example 2

[0063] Compared with Example 1, the solid composite polymer electrolyte does not contain polyethyleneimine and auxiliary additives, and the others remain the same.

[0064] Comparative Example 3

[0065] Compared with Example 1, no lithium salt ceramics were added, and the others remained the same.

[0066] For the first cycle charge and discharge capacity retention rates of the above embodiments and comparative examples at 1C, 2C, and 3C, the test results are shown in Table 1:

[0067]

[0068]

[0069] The above examples and comparative examples were subjected to needle puncture and extrusion tests. The test results are shown in Table 2:

[0070] Acupuncture pass rate Extrusion test pass rate Example 1 100%(2 / 2) 100%(2 / 2) Example 2 100%(2 / 2) 100%(2 / 2) Example 3 100%(2 / 2) 100%(2 / 2) Example 4 100%(2 / 2) 100%(2 / 2) Comparative Example 1 100%(2 / 2) 100%(2 / 2) Comparative Example 2 50%(1 / 2) 50%(1 / 2) Comparative Example 3 0%(0 / 2) 0%(0 / 2)

[0071] It can be seen from Table 1 that the capacity retention rates of the comparative examples are all lower than those of the embodiments, mainly because the solid composite polymer electrolytes in the three comparative examples lack inorganic lithium salts, polyethyleneimine and auxiliary additives, and no lithium salt ceramics are added. The lack of lithium salts and lithium salt ceramics will reduce the capacity retention rate of the battery, because the loss of lithium provided by the positive electrode during solid phase migration and electrochemical reactions during charging will consume lithium, and the lack of lithium salt supplementation, while the absence of polyethyleneimine and auxiliary additives, increases the crystallinity of polyethylene oxide and reduces the room temperature conductivity. The above factors lead to a capacity retention rate lower than that of the embodiments.

[0072] As shown in Table 2, the pass rate results of the needle puncture and extrusion tests show that the embodiment is higher than that of comparative examples 2 and 3. Comparative example 2 does not add thermosetting polyethyleneimine to form a cross-linked network structure, which reduces the mechanical properties of the solid composite electrolyte; comparative example 3 does not add ceramic lithium salt, which is equivalent to reducing a safety barrier between the positive and negative electrodes, so the pass rate in the safety test is 0%. Note: (2 / 2) means that both of the two batteries tested passed, (1 / 2) means that one of the two batteries tested passed, and (0 / 2) means that none of the two batteries tested passed.

[0073] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite positive electrode sheet, characterized in that: It comprises a positive electrode sheet and a solid composite polymer electrolyte layer covering the surface of the positive electrode sheet, wherein the solid composite polymer electrolyte layer comprises 10 to 30 parts by mass of polyethylene oxide, 20 to 50 parts by mass of polyethylene imine, 5 to 40 parts by mass of inorganic lithium salt, 5 to 15 parts by mass of additives and 5 to 30 parts by mass of plasticizer.

2. The composite positive electrode sheet according to claim 1, characterized in that: The relative molecular mass of the polyoxyethylene is between 8000 and 60000.

3. The composite positive electrode sheet according to claim 1, characterized in that: The relative molecular mass of the polyethyleneimine is between 3000 and 10000.

4. The composite positive electrode sheet according to claim 1, characterized in that: The inorganic lithium salt includes one or more of lithium fluoromethanesulfonate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium hexafluoroarsenate, lithium perchlorate, and lithium metaaluminate.

5. The composite positive electrode sheet according to claim 1, characterized in that: The additive is selected from one of aluminum oxide, silicon oxide, silicon oxide and polysiloxane.

6. The composite positive electrode sheet according to claim 1, characterized in that: The plasticizer includes vinyl carbonate or vinyl ethylene carbonate.

7. A solid-state battery without a diaphragm, characterized in that: A composite positive electrode sheet comprising any one of claims 1 to 6.

8. The membrane-free solid-state battery according to claim 7, characterized in that: It also includes a negative electrode sheet, the surface of which is covered with a lithium salt ceramic layer.

9. The membrane-free solid-state battery according to claim 8, characterized in that: The lithium salt ceramic component comprises polyvinylidene fluoride, lithium aluminum titanium phosphate and aluminum oxide, and the mass ratio is 1-3:3-5:8-12.

10. A method for preparing a solid-state battery without a diaphragm, characterized in that: The following steps are involved: Preparation of the composite positive electrode sheet of claims 1-6, comprising coating the surface of the positive electrode sheet with a solid composite polymer electrolyte and then drying; A diaphragm-free solid-state battery is obtained through the processes of rolling, slitting, laser cutting, die cutting, lamination, assembly, baking, formation and capacity division.

11. The method for preparing a diaphragm-free solid-state battery according to claim 10, characterized in that: It also includes preparing a composite negative electrode sheet, including coating a lithium salt ceramic on the surface of the negative electrode sheet and then drying it; A diaphragm-free solid-state battery is obtained through the processes of rolling, slitting, laser cutting, die cutting, lamination, assembly, baking, formation and capacity division.

12. The method for preparing a diaphragm-free solid-state battery according to claim 10, characterized in that: The solid composite polymer electrolyte is prepared by the following method: polyoxyethylene, polyethyleneimine, inorganic lithium salt, additives and plasticizers are placed in an oven for baking and drying respectively; a proper amount of NMP is taken as a solvent, a proper amount of PVDF is added, and polyoxyethylene, polyethyleneimine, plasticizer, inorganic lithium salt and additives are added respectively, stirred and dissolved, and dispersed evenly into slurry for later use.

13. The method for preparing a diaphragm-free solid-state battery according to claim 11, characterized in that: The lithium salt ceramic is prepared by the following method: using NMP as a solvent, first adding polyvinylidene fluoride to dissolve, then adding alumina and lithium aluminum titanium phosphate and stirring to obtain a lithium salt ceramic slurry for use.

Citation Information

Patent Citations

  • Composite solid electrolyte, preparation method thereof, and applications of composite solid electrolyte in all-solid-state lithium batteries

    CN107834104A

  • Diaphragm-free quasi-solid-state battery and preparation method of composite pole piece of diaphragm-free quasi-solid-state battery

    CN111799513A

  • Sulfonic acid functionalized polyethyleneimine polymer solid electrolyte

    CN113823831A

  • Functionalized microsphere with hollow structure and application of functionalized microsphere in all-solid-state lithium metal battery

    CN116284879A

  • Diaphragm-free semi-solid battery and preparation method and application thereof

    CN118315646A

Cited By

  • Separator-free solid-state battery, preparation method thereof and electric equipment

    CN120453480A